Consumer Protection Law in Sale and Purchase Transactions: A Perspective f Economic Justice and Sharia Ethic - Abd. Hamid; Zalina Binti Zakaria (Bulletin of Community Engagement, 2026)
This text examines consumer safety in sale and buy transactions through the lenses of financial justice and Sharia ethics, with precise interest in virtual marketplaces. Despite the existence of complete legal frameworks, customer protection law remains in large part procedural and reactive, failing to address structural electricity imbalance, information asymmetry, and unfair preferred contracts that systematically disadvantage clients. Using a socio-criminal studies layout, this observation integrates normative felony evaluation with maqāṣid al-sharīʿah as a great justice benchmark. The findings screen that conventional patron protection mechanisms often legitimize unequal transactions via prioritizing formal consent and contractual validity over fairness outcomes. digital systems in addition exacerbate customer vulnerability through centralizing control over information disclosure and dispute resolution. This newsletter proposes an integrative client protection model that mixes legal enforceability with Sharia-based totally ethical accountability, repositioning purchaser protection law as a preventive and justice-orientated regulatory framework. The take a look at contributes to patron law scholarship by way of demonstrating that Sharia ethics can be characterized as a normative evaluative framework that complements the legitimacy and effectiveness of client protection regulation in digital markets.